2021
DOI: 10.1002/wcs.1555
|View full text |Cite
|
Sign up to set email alerts
|

Building semantic memory from embodied and distributional language experience

Abstract: Humans seamlessly make sense of a rapidly changing environment, using a seemingly limitless knowledgebase to recognize and adapt to most situations we encounter. This knowledgebase is called semantic memory. Embodied cognition theories suggest that we represent this knowledge through simulation: understanding the meaning of coffee entails re-instantiating the neural states involved in touching, smelling, seeing, and drinking coffee. Distributional semantic theories suggest that we are sensitive to statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 125 publications
2
26
0
Order By: Relevance
“…80%) are typically learnt not in real life situations where reference objects and actions are present in the environment of the communicating individuals, but rather from texts (Kintsch, 1974(Kintsch, , 1998. So-called 'hybrid models' of semantics and concepts (Andrews et al, 2009;Davis & Yee, 2021;Glenberg & Robertson, 2000;Harnad, 1990;Louwerse & Jeuniaux, 2010) take into account both relevant facts, that at least some concepts and symbols require conceptual 'grounding' in specific sensorimotor information from the world, that is, in concept-related objects, actions or their features, and that, after such grounding has happened, distributional or other types of learning relating symbols to symbols can function via contextual transfer of conceptual information. The learning of symbolic meaning by way of previously grounded symbols is sometimes called 'indirect grounding', 'grounding transfer' or 'symbolic theft' and is now supported by ample evidence both from behavioural experiments and computational models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…80%) are typically learnt not in real life situations where reference objects and actions are present in the environment of the communicating individuals, but rather from texts (Kintsch, 1974(Kintsch, , 1998. So-called 'hybrid models' of semantics and concepts (Andrews et al, 2009;Davis & Yee, 2021;Glenberg & Robertson, 2000;Harnad, 1990;Louwerse & Jeuniaux, 2010) take into account both relevant facts, that at least some concepts and symbols require conceptual 'grounding' in specific sensorimotor information from the world, that is, in concept-related objects, actions or their features, and that, after such grounding has happened, distributional or other types of learning relating symbols to symbols can function via contextual transfer of conceptual information. The learning of symbolic meaning by way of previously grounded symbols is sometimes called 'indirect grounding', 'grounding transfer' or 'symbolic theft' and is now supported by ample evidence both from behavioural experiments and computational models (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Future research should try to study other potential moderating effects of relevant variables on the relations between amodal maturational processes and emotional propagative processes. Recent reviews of the study of the interaction between the affective and semantic properties of words have brought up the need to regard them as part of a whole system (e.g., Barsalou, Dutriaux, & Scheepers, 2018; Davis & Yee, 2021; Winkielman, Coulson, & Niedenthal, 2018). As stated by Ostarek and Huettig (2019), new paradigms should be endorsed to advance embodiment research.…”
Section: Discussionmentioning
confidence: 99%
“…But the activation of modal representations seems to participate in language processing more than expected in a system formed by purely amodal symbols (e.g., Binder, Westbury, McKiernan, Possing, & Medler, 2005;Hauk, Johnsrude, & Pulvermüller, 2004;Zwaan & Yaxley, 2003;Nastase & Haxby, 2017;Davis & Yee, 2021;Vergallito, Petilli, Cattaneo, & Marelli, 2019). Thus, there is also a need to formalize an embodiment process to deal with the classical claims of the symbol grounding problem (Harnad, 1990;Searle, 1980), as some amodal representations should be grounded to avoid the Chinese Room Argument (Searle, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…The embodied approach argues that processing conceptual representations requires eliciting sensorimotor experiences, for example, by simulating them (Von Hofsten, 2007). Motor representations are then automatically elicited when we activate conceptual representations (Aziz-Zadeh & Damasio, 2008;Galetzka, 2017;Meteyard et al, 2012), as shown in the context of language (Borghi et al, 2019;Borghi & Binkofski, 2014;Borghi & Cimatti, 2010;Davis & Yee, 2021;Hauk et al, 2004). Note that here the term "sensorimotor experiences" should be intended broadly, to encompass multiple exteroceptive, proprioceptive and interoceptive modalities -all of which can become linked to action representation during the learning of likelihood mappings.…”
Section: Figure 5 Results Of Simulation 3: How the Generative Model I...mentioning
confidence: 99%